Crescimento de filmes finos de NbN por magnetron sputtering reativo - Souza, Paloma Boeck (2013)
In the last decades, several applications of niobium nitride thin films has been proposed or effectively implemented. In the cubic δ − NbN phase, the bulk material presents a Tc for the superconducting transition near 17 K, what is far larger than those found in other normal (BCS) superconductors and useful in, for example, Josephson tunnel junctions. More recently, other phases have been also focus of interest, like the hexagonal δ-NbN phase. The hardness and resistance to chemical corrosion make this material well fitted for mechanically improved surface. Thin film preparation or deposition of niobium nitrides by physical methods (PVD) is not a trivial task. Stoichiometry, crystal structure and morphology of the resulting films are strongly affected by the deposition conditions, and even a qualitative model for the growth mechanisms of niobioum nitride is still lacking. In this work we have studied the effect of some parameters on the structural and morphologic properties of NbN thin films. The samples have been produced by reactive magnetron sputtering for different nitrogen partial pressures, substrate temperatures, bias voltages and deposition times. The crystallographic structure, preferred orientations, grain sizes and surface roughness were stablished by XR diffraction and, for some samples, atomic force microscopy. The results have shown that without bias voltage cubic NbN thin films are obtained, with or without substrate heating, when the partial pressure of N2 in the reactive atmosphere is between 13 and 25 %. Films produced with 17 % N2 are preferentially oriented in the <200> direction and this texture is enhanced by substrate heating. The analysis of the results in two samples with different thickness clearly indicates that for cubib NbN, the growth is remarkable different in the <111> and <200> directions. A possible mechanism to explain this difference is presented. The main effect of the voltage bias was to induce a hexagonal δ - NbN structure even for voltages as low as -10 V. These films present larger densities values than those found in the films with cubic phase, being the highest density achieved with -70V bias. All samples deposited with bias present a compressive stress and small grain size. The connections between stress, grain size and density are presented and discussed. In summary, we have identified a group of key parameters that makes possible the deposition of NbN thin films by reactive magnetron sputtering, either for superconductivity or tribological applications.